PENERAPAN METODE SOSIODRAMA UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN - Suparji Suparji (JURNAL PENDIDIKAN ROKANIA, 2017)
Sociodrama method for improve learning outcomes civic education students of class VI SD Negeri 014 Rambah Hilir Kabupaten Rokan Hulu. The sociodrama method is way of teaching to give chance for students and perform certain role playing activities to teching and learning concerning human behavior in community life with social purpose. This method can to improve ability learning of civic education for students of class VI SD Negeri 014 Rambah Hilir, this is proven with this method the students very excited for study and can to expressed his opinion. Using this method the writer to present lesion the material in away gives the activities for students for gives good deeds both physical and non physical. And than preparation were done on the basis of an event in a predetermined situation and condition. Proved to be an increase of cycle I until cycle II this learning is success